Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve the equation [tex]\(\log (t - 3) = \log (17 - 4t)\)[/tex], follow these detailed steps:
1. Understand the property of logarithms:
The equation [tex]\(\log (a) = \log (b)\)[/tex] implies that [tex]\(a = b\)[/tex], provided [tex]\(a\)[/tex] and [tex]\(b\)[/tex] are both positive.
2. Apply the property:
Given [tex]\(\log (t - 3) = \log (17 - 4t)\)[/tex], we can set the arguments of the logarithms equal to each other:
[tex]\[ t - 3 = 17 - 4t \][/tex]
3. Solve for [tex]\(t\)[/tex]:
- Start by isolating [tex]\(t\)[/tex] on one side. Add [tex]\(4t\)[/tex] to both sides to combine the [tex]\(t\)[/tex] terms:
[tex]\[ t + 4t - 3 = 17 \][/tex]
This simplifies to:
[tex]\[ 5t - 3 = 17 \][/tex]
- Next, add 3 to both sides to isolate the term with [tex]\(t\)[/tex]:
[tex]\[ 5t - 3 + 3 = 17 + 3 \][/tex]
This simplifies to:
[tex]\[ 5t = 20 \][/tex]
- Finally, divide by 5 to solve for [tex]\(t\)[/tex]:
[tex]\[ t = \frac{20}{5} = 4 \][/tex]
4. Check the solution:
For the solution [tex]\(t = 4\)[/tex] to be valid, the arguments of the original logarithms must be positive:
- Check [tex]\(t - 3 > 0\)[/tex]:
[tex]\[ 4 - 3 = 1 > 0 \][/tex]
- Check [tex]\(17 - 4t > 0\)[/tex]:
[tex]\[ 17 - 4 \times 4 = 17 - 16 = 1 > 0 \][/tex]
Both conditions are satisfied, so the solution [tex]\(t = 4\)[/tex] is valid.
Therefore, the solution to the equation [tex]\(\log (t - 3) = \log (17 - 4t)\)[/tex] is [tex]\(\boxed{4}\)[/tex].
1. Understand the property of logarithms:
The equation [tex]\(\log (a) = \log (b)\)[/tex] implies that [tex]\(a = b\)[/tex], provided [tex]\(a\)[/tex] and [tex]\(b\)[/tex] are both positive.
2. Apply the property:
Given [tex]\(\log (t - 3) = \log (17 - 4t)\)[/tex], we can set the arguments of the logarithms equal to each other:
[tex]\[ t - 3 = 17 - 4t \][/tex]
3. Solve for [tex]\(t\)[/tex]:
- Start by isolating [tex]\(t\)[/tex] on one side. Add [tex]\(4t\)[/tex] to both sides to combine the [tex]\(t\)[/tex] terms:
[tex]\[ t + 4t - 3 = 17 \][/tex]
This simplifies to:
[tex]\[ 5t - 3 = 17 \][/tex]
- Next, add 3 to both sides to isolate the term with [tex]\(t\)[/tex]:
[tex]\[ 5t - 3 + 3 = 17 + 3 \][/tex]
This simplifies to:
[tex]\[ 5t = 20 \][/tex]
- Finally, divide by 5 to solve for [tex]\(t\)[/tex]:
[tex]\[ t = \frac{20}{5} = 4 \][/tex]
4. Check the solution:
For the solution [tex]\(t = 4\)[/tex] to be valid, the arguments of the original logarithms must be positive:
- Check [tex]\(t - 3 > 0\)[/tex]:
[tex]\[ 4 - 3 = 1 > 0 \][/tex]
- Check [tex]\(17 - 4t > 0\)[/tex]:
[tex]\[ 17 - 4 \times 4 = 17 - 16 = 1 > 0 \][/tex]
Both conditions are satisfied, so the solution [tex]\(t = 4\)[/tex] is valid.
Therefore, the solution to the equation [tex]\(\log (t - 3) = \log (17 - 4t)\)[/tex] is [tex]\(\boxed{4}\)[/tex].
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.